Defending women's rights in Europe : gender equality and EU enlargement - Avdeyeva, Olga A., 1976- (Albany : State University of New York Press, 2015)
Comparative analysis of gender equality reforms enacted in ten post-communist states who became members of the European Union. Between 2004 and 2007, ten post-communist Eastern European states became members of the European Union (EU). To do so, these nations had to meet certain EU accession requirements, including antidiscrimination reforms. While attaining EU membership was an incredible achievement, many scholars and experts doubted the sustainability of accession-linked reforms. Would these nations comply with EU directives on gender equality? To explore this question, Defending Women's Rights in Europe presents a unique analysis of detailed original comparative data on state compliance with EU gender equality requirements. It features a comprehensive quantitative analysis combined with rigorous insightful case studies of reforms in Poland, the Czech Republic, and Lithuania. Olga A. Avdeyeva reveals that policy and institutional reforms developed furthest in those states where women's advocacy NGOs managed to form coalitions with governing political parties. After becoming members of the EU, the governments did not abolish these policies and institutions despite the costs and lack of popular support. Reputational concerns prevented state elites from policy dismantling, but gender equality policies and institutions became marginalized on the state agenda after accession. Olga A. Avdeyeva is Associate Professor of Political Science at Loyola University Chicago.
Acknowledgments -- Eu enlargement, accession conditionality, and gender equality : theoretical departures and research design -- Introduction -- Theoretical framework -- Exploring the data -- Case studies : international and domestic dimensions -- Introduction to qualitative analysis -- Poland : political swings and challenged compliance -- Czech Republic : state cooptation of reforms and marginal compliance -- Lithuania : policy emulation and strong compliance -- Conclusion -- Notes -- Appendices -- List of interviews -- Bibliography -- Index.
Includes bibliographical references and index.
Print version record.
English.
Keywords: Women's rights -- European Union countries; Sex discrimination against women -- European Union countries; Femmes -- Droits -- Pays de l'Union européenne.; Discrimination à l'égard des femmes -- Pays de l'Union européenne.; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Sex discrimination against women; Women's rights; European Union countries; Erweiterung; Frau; Recht; Gleichberechtigung; Frauenpolitik; Europäische Union; Osteuropa; Kvinnors rättigheter.; Kvinnoförtryck.